Pentoxifylline Inhibits Pulmonary Fibrosis by Regulating Cellular Senescence in Mice - Lin, Yifan; Xu, Zhihao; Zhou, Beibei; Ma, Keer; Jiang, Mengyi (Frontiers in Pharmacology, 2022)
Idiopathic pulmonary fibrosis (IPF) is a chronic progressive disease, and its occurrence and development are mediated by cellular senescence. Drugs targeting senescent cells seem like a promising and efficacious strategy for IPF treatment. Previous studies have illustrated that pentoxifylline (PTX) may play a certain role in inhibiting pulmonary fibrosis and combating cellular senescence. In this study, we demonstrated that PTX administration inhibits pulmonary fibrosis development and cellular senescence in the bleomycin (BLM)-induced IPF mice model. Moreover, the expression levels of fibrosis-related genes and senescence-related genes in mice lung tissue and primary pulmonary fibroblasts illustrated lung fibroblasts’ vital role in these two processes. And the curative effect of PTX was completed mainly by acting on lung fibroblasts. Besides, during the whole treatment, delayed initiation or advanced halt of PTX administration would influence its effectiveness in reducing fibrotic and senescent traits in various degrees, and the latter influenced more. We further determined that a long period of PTX administration could bring noticeable benefits to mice in recovering BLM-induced lung fibrosis and suppressing age-associated cellular senescence. Moreover, it was still effective when PTX administration was used to treat senescent human fibroblasts. Thus, our findings manifested that PTX therapy is an efficient remedy for pulmonary fibrosis by suppressing cellular senescence.